Antibacterial effect and cytotoxic effect of supercritical extraction of thyme and thyme extract obtained through hydrodistillation process - Mišić Dušan; Nišavić Jakov; Žižović Irena; Ivanović Jasna (Veterinarski Glasnik, 2009)
Investigations of antibacterial effect of supercritical extraction of thyme (TNKE) and thyme extract obtained by hydrodistillation (THD) covered 18 bacteria strains from the genuses Staphylococcus, Streptococcus and Enterococcus, including the strains MRSA, the strains VRE, as well as the reference strains S.pyogenes ATCC 19615, S. agalactiae ATCC 27959, S. aureus ATCC 11632, and S.aureus ATCC 25923. The anibacterial effect of thyme extracts was examined using the microdillution method in bouillon, and the cytotoxic effect of thyme extract was examined on the VERO cell line. The obtained values for MIC THD extract ranged from 160μg/mL to 1280μg/mL for all bacteria strains covered by the investigations. The obtained values for MIC TNKE extract were 1280 μg/mL to 2560 μg/mL for all examined strains except for 1 strain of S. intermedius of 320 μg/mL. The examined extracts revealed a cytotoxic effect on the VERO cell line in concentrations higher than 40 μg/mL.